Islamic Management and Leadership at the Musthafawiyah Purbabaru Islamic Boarding School - Efendi, Manahan; Syafnan; Nurhayani (RADINKA JAYA UTAMA PUBLISHER, 2024)
The Musthafawiyah Islamic Boarding School in North Sumatra stands as one of the oldest and largest pesantren, showcasing resilience through its adherence to Islamic values in management and leadership. This study aims to explore the management strategies and distinctive leadership models implemented at this pesantren, alongside their impact on shaping students' character. Using a qualitative approach and case study method, data were gathered through in-depth interviews, direct observations, and document analysis. The findings reveal a well-structured hierarchical management system with clearly defined responsibilities. Leadership at the pesantren is rooted in spiritual authority, emphasizing Islamic values such as justice, consultation, and exemplary behavior. This leadership model significantly contributes to the formation of students who are religious, self-reliant, and ethical. Nonetheless, challenges such as modernization, technological advancements, and global demands require innovative adaptations without compromising the pesantren's traditional essence. This research highlights the importance of integrating Islamic principles into pesantren management and leadership as a means of enhancing educational quality and navigating contemporary challenges. Recommendations include strengthening human resource capabilities, incorporating technology into teaching, and aligning the curriculum with global needs. These findings aim to inspire the development of Islamic education models in other pesantren and beyond.